An In Vitro System to Study Sertoli Cell Blood-Testis Barrier Dynamics - Mruk, Dolores D. (2011)
The use of an in vitro system based on primary cultures of Sertoli cells isolated from rat testes has greatly facilitated the study of the blood-testis barrier in recent years. Herein, we summarize the detailed procedures on the isolation of undifferentiated Sertoli cells from 20-day-old rat testes, the culture of these cells as a monolayer on Matrigel-coated bicameral units, the characterization of these cultured cells, and the use of the Sertoli cell epithelium for monitoring the integrity of the Sertoli cell blood-testis barrier. This information is based on the routine use of this system in our laboratory to study the Sertoli cell blood-testis barrier in the past two decades, which should be helpful for investigators in the field.